New formulation of ductility reduction factor of RC frame-wall dual systems for design under earthquake loadings. Issue 138 (November 2020) - Zerbin, Matteo; Aprile, Alessandra; Spacone, Enrico
Abstract: Any design of standard structures in keeping with seismic safety norms is usually founded on an approach characterised by force-based design. Research has proven, over the course of several decades, that such an approach has a solid basis and can easily be applied by the engineers in charge of the design project. Furthermore, when taken in conjunction with principles of capacity design, the force-based approach is effective against premature structural failures. The force-based design approach, however, suffers from a number of shortcomings, especially regarding the way it has been employed in seismic design codes of recent years. One of the weaknesses can be attributed to the way the base shear is calculated via a reduction factor that has been defined a priori and that remains constant for a certain structural system typology. The outcome of depending on the same design input shows that structures identical in type but variant in geometry undergo varying ductility demands and exhibit, therefore, a different seismic performance. In this research, a procedure for assessing force-reduction factors of RC frame-wall dual systems is developed, by combining the analytical formulations proposed by Zerbin et al. (2019) for wall and frame systems, separately. These analytical formulations make it possible to combine global and local ductility demands, thereby allowing a calculation of the factors of force ductility reduction that result in balanced local ductility demands and the predicted levels of damage. The proposed method is based on empiric expressions that merely require – as input data – the information available when starting the design process. The proposed formulation is applied to a set of frame-wall structures and tested by means of both nonlinear static and dynamic analyses. The current study has produced conclusions showing that, with respect to such dual system structures' seismic behaviour, the procedure proposed herein yields a more accurate assessment of than the approach being currently used by design guidelines; in turn this method may provide a valid contribution to the evolving guidelines of future seismic design codes. Highlights: Alternative formulation for computing force reduction factors for dual structures. Simple analytical and empiric models which only require available input data. Providing a variable force reduction factor not constant for a structural system. Obtaining a similar seismic performance for structures of different geometry. Providing a more accurate ductility reduction factor than current design approach.